2013
DOI: 10.1042/cs20120240
|View full text |Cite
|
Sign up to set email alerts
|

Ribonucleotide reductase small subunit M2 serves as a prognostic biomarker and predicts poor survival of colorectal cancers

Abstract: The overexpression of RRM2 [RR (ribonucleotide reductase) small subunit M2] dramatically enhances the ability of the cancer cell to proliferate and to invade. To investigate further the relevance of RRM2 and CRCs (colorectal cancers), we correlated the expression of RRM2 with the clinical outcome of CRCs. A retrospective outcome study was conducted on CRCs collected from the COH [(City of Hope) National Medical Center, 217 cases] and ZJU (Zhejiang University, 220 cases). IHC (immunohistochemistry) was employed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 43 publications
6
74
0
Order By: Relevance
“…RRM2 is known to function as a tumor driver during carcinogenesis and high expressed in esophageal cancer, gastric cancer, colon cancer, and hepatocellular cancer [21][22][23][24][25]. This study also showed that RRM2 was higher expressed in most PTC samples and seemed to be more intensively stained in UTC tissues.…”
Section: Discussionsupporting
confidence: 57%
“…RRM2 is known to function as a tumor driver during carcinogenesis and high expressed in esophageal cancer, gastric cancer, colon cancer, and hepatocellular cancer [21][22][23][24][25]. This study also showed that RRM2 was higher expressed in most PTC samples and seemed to be more intensively stained in UTC tissues.…”
Section: Discussionsupporting
confidence: 57%
“…Antibodies against RRM2 and RRM2B were previously generated, selected and tested in our lab [23]. Antibodies against ER (Clone: SP1), PR (Clone: PgR636), HER2 (Clone: A0485) and Ki67 (Clone: MIB-1) were purchased from Dako company, and the p53 antibody (Clone: DO-7) was purchased from Vector Lab.…”
Section: Methodsmentioning
confidence: 99%
“…RRM2 depletion significantly reduced antiapoptotic protein Bcl-2 expression and RRM2 suppression led to increased Bcl-2 degradation 10. RRM2 was reported to play an active role in tumor progression11 and elevated RRM2 levels were correlated with poor prognosis for patients with colorectal cancer, pancreas adenocarcinoma, lung adenocarcinoma, and ovarian cancer 1215. RRM2 was overexpressed in human HCC 16,17.…”
Section: Introductionmentioning
confidence: 99%